Introduction: global order in the age of Trump - Böller, Florian; Werner, Welf (Hegemonic transition, 2021)
The current international order is unraveling. Under the Trump administration, the traditional hegemon, the US, has ceased to unequivocally support the institutions it helped to foster. At the same time, China’s power surge, contestation by smaller states, and the West’s internal struggles with populism and economic discontent have undermined the liberal order from the outside, and from within. While a diagnosis of this crisis is hardly new, its sources, scope, and underlying politics are still up for debate. The introductory chapter of the volume presents the analytical framework for the subsequent case studies. Hegemony is here understood not only as material stratification and the predominance of one actor in terms of military resources and economic power, but also includes ideational aspects since the concrete form of hegemony is characterized by specific rules and norms. It follows that the transformation or breakdown of a hegemonic order can be identified if one or more of the following processes take place: (1) the material configuration significantly shifts; (2) core norms, rules, and institutions break down; (3) social relations between leaders and followers change. Following this perspective, the case studies in this volume will focus on the dynamic politics of hegemonic order. This perspective includes domestic support and the demand for specific hegemonic goods, the contestation and support by other actors within distinct layers of hegemonic orders, and the underlying bargaining between the hegemon and subordinate actors.
Gesehen am 20.10.2025